Association between Gender and Anxiety among Covid-19 Patients: A Meta-Analysis - Zuraida Zulkarnain; Arum Nuryati; Desif Upix; Adilla Misi; Andi Siswanto; Atik Handariati; Zadia Dara; Alfiana Nur Nur Rohmani; Saryanto Saryanto (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: The COVID-19 outbreak rapidly spread worldwide, with a significant number of cases and deaths causing anxiety, especially among the sufferers. Biologically, males and females show different psychological responses to the events at hand. This study aimed to examine the association between gender and anxiety among COVID-19 patients.Subjects and Method: This study was a meta-analysis. The articles were obtained from databases PubMed and Scopus using keywords